The Developing a Valid and Reliable Assessment Instrument for Academic Essay Writing in Higher Education - M. Hilmy Hidayatullah; Nadrotin Mawaddah; Nur Mukminatien; Suhono, Suhono; Mukminatus Zuhriyah; Nahid Ayad; Yeasy Agustina Sari (Bulletin of Science Education, 2025)
Many university instructors assess academic essay writing using general rubrics or borrowed instruments that do not align with specific course outcomes and learner profiles. This study was initiated to address this gap by developing a valid and reliable assessment instrument for academic essay writing among EFL university students, focusing on argumentative essays. The instrument was constructed systematically, involving needs analysis, expert validation, pilot testing, and statistical evaluation for reliability and validity. The trial was conducted with 6 students from the English Language Education Study Program, and their essays were rated by two trained raters. The results showed that the rubric successfully captured performance variation across six key writing components and allowed for consistent scoring with minimal discrepancies between raters. Expert validators confirmed that the rubric is clear, relevant, and aligned with academic essay writing expectations. Rater reliability analysis showed consistent inter-rater scores (score differences ≤1 point), indicating strong rubric usability. Based on these findings, this instrument offers a practical and theoretically grounded tool for assessing academic essay writing in EFL higher education settings.